Integrated Reporting in Sub-Saharan Africa: A Systematic Review of Outcomes, Constraints and Impacts - Abbana, Sharanam; Marimuthu, Ferina; Maama, Haruna (Journal of Ecohumanism, 2025)
Integrated Reporting (IR) integrates financial and non-financial information to provide a holistic account of how organisations create and sustain value. While the International IR Framework provided a global reference point in 2013, IR in practice has evolved more broadly, encompassing diverse sustainability and governance disclosures beyond any single framework. Since its emergence, IR has attracted growing international attention, yet its adoption and effectiveness across Sub-Saharan Africa (SSA) remain limited and uneven. This paper conducts a systematic literature review (SLR) of 40 peer-reviewed studies published between 2015 and 2024, guided by PRISMA guidelines, to synthesise evidence on the outcomes, constraints, drivers, and impacts of IR, with an emphasis on SSA. The review addresses four research questions linked to testable hypotheses. Evidence supports that IR enhances strategic outcomes such as transparency, trust, and legitimacy (RQ1/H1), but constraints including symbolic adoption, weak assurance, and fragmented regulation undermine its consistency (RQ2/H2 not supported). Adoption and quality are influenced by both internal capabilities and external pressures (RQ3/H3 partially supported) yet operate inconsistently across contexts. Organisational impacts (RQ4/H4) are mixed: while IR can improve valuation and capital access, outcomes are highly contingent on governance quality, assurance credibility, and institutional maturity. The findings highlight persistent spatial, methodological, and theoretical gaps, underscoring the need for context-sensitive approaches to IR in SSA. This study contributes to theory, practice, and policy by clarifying when, why, and for whom IR delivers meaningful outcomes in emerging markets.